1999
DOI: 10.1016/s0895-7061(98)00253-2
|View full text |Cite
|
Sign up to set email alerts
|

Family history of essential hypertension versus obesity as risk factors for hypertension in adolescents

Abstract: Family history of hypertension and obesity are both risk factors for hypertension. Hypertension and obesity share several physiopathologic abnormalities and are frequently associated. However, not all obese people are hypertensive. Renal handling of sodium has been proposed as a physiopathogenic mechanism of essential hypertension and obesity. This study was conducted in obese adolescents to evaluate the role of a family history of hypertension versus obesity in the renal handling of sodium. .5% ؎ 1.3%, in ON … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 15 publications
1
24
1
1
Order By: Relevance
“…These findings are consistent with previous reports of a linkage between hypertension and obesity in children and adults (5,25,28). For the primary prevention of hypertension, a strategy to checkup on obese children with hyperinsulinemia, that is visceral fat accumulation, is required.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are consistent with previous reports of a linkage between hypertension and obesity in children and adults (5,25,28). For the primary prevention of hypertension, a strategy to checkup on obese children with hyperinsulinemia, that is visceral fat accumulation, is required.…”
Section: Discussionsupporting
confidence: 91%
“…SNS hyperactivity via hyperleptinemia probably affected SBP elevation in OF subjects rather than in ON subjects. Previous studies have demonstrated that hyperinsulinemia, hyperleptinemia, SNS hyperactivity and hyperactivity of the renin-angiotensin system caused renal and hemodynamic alterations associated with renal sodium retention, and consequential hypertension (5,26,28). In the present study, this linkage may have affected children in the OF rather than those in the ON group.…”
Section: Discussionmentioning
confidence: 52%
“…Given the important effects of gender on leptin levels, the genetic contribution to leptin may differ between men and women [28,49,50]. Several studies have noted abnormal glucose and insulin metabolism in normotensive offspring of families with hypertension [28,[50][51][52][53]. In those studies, a positive family history of hypertension also predicted other risk factors, such as higher levels of plasma norepinephrine [29], body weight [54], insulin [53], and abnormal lipid metabolism.…”
Section: Familial Obesity and Hypertensionmentioning
confidence: 99%
“…This observation agreed with the finding of Simsolo et al and Muratova et al that overweight positively related with hypertension. 20, 21 Sundar et al found, an overwhelming evidence in his study that the prevalence of hypertension was high among obese individuals (p=0.000), which was highly significant. Similar observation was seen by Buch et al 8,15 The prevalence of hypertension was much higher among those students (8%) with positive family history, compared to 5.2%, where family history of hypertension was absent, which was statistically significant (p<0.05).…”
Section: Association Of Blood Pressure With Several Variables/charactmentioning
confidence: 88%